2018
DOI: 10.1002/jts.22295
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Psychological and Pharmacological Treatments for Adjustment Disorder in Adults

Abstract: Adjustment disorder is a common psychiatric disorder, yet knowledge of the efficacious treatments for adjustment disorder is limited. In this systematic review, we aimed to examine psychological and pharmacological interventions that target adjustment disorder in adults to determine which interventions have the best evidence for improving adjustment disorder symptoms. We performed database searches for literature published between January 1980 and September 2016 and identified studies that included both a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Psychotherapeutic and psychopharmacological treatment options for AD have recently been summarized in three review articles (Domhardt and Baumeister, 2018;O'Donnell et al, 2018;Stein, 2018). They found that the quality of evidence has been ranked low to very low (O'Donnell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychotherapeutic and psychopharmacological treatment options for AD have recently been summarized in three review articles (Domhardt and Baumeister, 2018;O'Donnell et al, 2018;Stein, 2018). They found that the quality of evidence has been ranked low to very low (O'Donnell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Psychotherapeutic and psychopharmacological treatment options for AD have recently been summarized in three review articles (Domhardt and Baumeister, 2018;O'Donnell et al, 2018;Stein, 2018). They found that the quality of evidence has been ranked low to very low (O'Donnell et al, 2018). McPhillips et al (2018) provide qualitative data on why MCT might be more effective than cognitive behavioral therapy (CBT) in the treatment of emotional distress in cardiac patients, although the validity of this hypothesis still needs to be shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is only one published systematic review of treatments available for adjustment disorder. A 2018 review examined 29 treatment trials investigating current options for psychological and pharmacological intervention [52]. They found that the quality of evidence in these studies was “low” to “very low” according to Grading of Recommendations Assessment, Development and Evaluation (GRADE; [53]) guidelines.…”
Section: Treatment and Interventionmentioning
confidence: 99%
“…Individuals who cannot accept their own social status on the basis of the Japanese traditional hierarchal order can exhibit depression-like behaviors, such as learned helplessness and social withdrawal, which is considered to indicate the presence of MTD (Kato, Hashimoto, et al, 2016;Kato & Kanba, 2017). Given that MTD is a subtype of adjustment disorders that are F I G U R E 2 Changes of social rank and depression-like symptoms resistant to psychotropic drugs (O'Donnell, Metcalf, Watson, Phelps, & Varker, 2018), medication is likely to be ineffective. In this article, we have reviewed the potential mechanisms of MTD from the standpoint of social status using knowledge gained mainly from captive animals and humans and have proposed that a shared pathobiology mechanism underlies social status and MTD.…”
Section: Con Clus Ionmentioning
confidence: 99%